2014
DOI: 10.3168/jds.2013-7622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of ration composition on income over feed cost and milk yield

Abstract: Feed is generally the greatest expense for milk production. With volatility in feed and milk markets, income over feed cost (IOFC) is a more advantageous measure of profit than simply feed cost per cow. The objective of this study was to evaluate the effects of ration cost and ingredient composition on IOFC and milk yield. The Pennsylvania State Extension Dairy Team IOFC tool (http://extension.psu.edu/animals/dairy/business-management/financial-tools/income-over-feed-cost/introduction-to-iofc) was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 10 publications
5
31
0
6
Order By: Relevance
“…The highest MY group had the lowest costs for the breeding operations (0.17 ± 0.02 CZK). Increasing milk yields leave the total cost per L and net margin per L relatively unchanged, but the increased milk output substantially boosts the herd's total profit (Buza et al, 2014). Kvapilík et al (2013) and Heikkilla et al (2008) found that the price movements for milk, the components in milk, and the production inputs can significantly affect the farm profitability and that the management should therefore adapt to these changes.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%
“…The highest MY group had the lowest costs for the breeding operations (0.17 ± 0.02 CZK). Increasing milk yields leave the total cost per L and net margin per L relatively unchanged, but the increased milk output substantially boosts the herd's total profit (Buza et al, 2014). Kvapilík et al (2013) and Heikkilla et al (2008) found that the price movements for milk, the components in milk, and the production inputs can significantly affect the farm profitability and that the management should therefore adapt to these changes.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%
“…O produtor empresário precisa, entre outras coisas, considerar a informação como um insumo de grande importância, conhecer o mundo onde está inserido o seu sistema de produção (da porteira para fora) e, também, conhecer bem o seu sistema de produção (da porteira para dentro) 2 . Com a apuração dos custos de produção, podem-se adotar estratégias gerencias na intenção de minimizá-los e aumentar a lucratividade 3 , avaliar o efeito da escala de produção 4 , do tipo de sistema de criação e mão-de-obra 2 , bem como comparar a rentabilidade de sistemas de produção 5 . Assim, objetivou-se com este estudo comparar alguns indicadores econômicos e identificar os componentes que exerceram maior influência sobre o custo operacional efetivo de fazendas leiteiras com alto volume de produção, em sistemas de confinamento total.…”
unclassified
“…Feed is the greatest expense in milk production (Buza et al, 2014). Knowledge of the individual dairy cow's voluntary dry matter intake (DMI) could contribute to the design of more efficient animal nutrition, at either the group level, summing more accurate predictions of all individual cows concurrently presented in a group (Maltz et al, 2013) or the individual cow level.…”
Section: Introductionmentioning
confidence: 99%